The species of Bursera (Burseraceae) in the upper Rio Papaloapan Depression (Mexico) - Rzedowski, Jerzy; Medina Lemus, Rosalinda; Calderón de Rzedowski, Graciela (Instituto de Ecología, A.C., 2004)
The upper Papaloapan river basin is defined in this paper as the southwestern part of this hydrologic region situated above the 400 m contour line, thus embracing an area of approximately 21,000 km2, shared between the Mexican states of Oaxaca, Puebla and Veracruz. On the basis of a study of more than 900 collections of Bursera from the region, the existence of 21 species is documented. Two of these (B. graveolens (H.B.K.) Tr. & Planch. and B. hintonii Bullock) were previously unreported from the area. For one species the name B. linanoe (La Llave) comb. nova is proposed as legitimate for the plant known as B. aloexylon (Schiede ex Schltdl.) Engl. Three additional species (B. altijuga, B. esparzae and B. pontiveteris, all belonging to the section Bullockia)) are described as new. A lectotype is also designated for B. submoniliformis Engl., as well as a neotype for Amiris linanoe La Llave. An identification key is provided for all the species, as well as descriptions, synonymy, illustrations, distribution maps and information concerning local names, uses and ecological preferences. A brief phytogeographical discussion is also given. In addition, a summary of the taxonomic history of Bursera, including its nomenclatural complexities, is provided.